SECURE PASSWORD MANAGEMENT AND WPA CRACKING: A DUAL APPROACH LEVERAGING CRYPTOGRAPHIC DESIGN AND HIGH-PERFORMANCE COMPUTING - Himansu Pandey; Aryan; Aukta, Sahil; Sudesh (International Journal of Research -GRANTHAALAYAH, 2024)
This project presents a dual-focused investigation into secure password management and high-performance cryptographic analysis. The first part involves the design and implementation of a secure, user-friendly password manager that employs strong encryption, multi-factor authentication (MFA), auto-fill features, and secure cloud synchronization. This system aims to mitigate security risks associated with weak or reused credentials by offering advanced password generation, storage, and retrieval capabilities. The second part of the project evaluates the efficiency of the Cell Broadband Engine (Cell BE) processor—most notably used in the PlayStation 3—for brute-force WPA password cracking. This includes in-depth studies of WPA vulnerabilities, brute-force attack algorithms, and the adaptation of cryptographic procedures to leverage the parallel architecture of the Cell BE. By applying the adapted A³ development model, which integrates application requirements, algorithm design, and architecture-specific implementation, the project explores the performance potential and practical feasibility of using Cell BE for cryptographic operations. The findings demonstrate both the effectiveness of the password manager in real-world use and the capability of the Cell BE architecture in accelerating WPA brute-force cracking tasks.